PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode - Rizkia Ayu Salsabila Rosyidi; Eni Dwi Susliyanti; Cesilia Arum Septianingsih; Andi Urfia Awaliah (Juremi: Jurnal Riset Ekonomi, 2024)
This research was conducted to examine the effect of profitability, firm size and firm growth on firm value and to test moderation using the capital structure in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. Data obtained from the Indonesia Stock Exchange (IDX) website, www.idx.co.id. The method used was purposive sampling with a final data sample 31. The data analysis used was t test and Moderated Regression Analysis (MRA). The results of this study indicate that profitability has a significant positive effect on firm value while firm size and firm growth have an insignificant negative effect on firm value and capital structure is not able to moderate the profitability of company size and firm growth on firm value